Downregulation of TLR4 by miR-181a Provides Negative Feedback Regulation to Lipopolysaccharide-Induced Inflammation - Jiang, Kangfeng; Guo, Shuai; Zhang, Tao; Yang, Yaping; Zhao, Gan; Shaukat, Aftab; Wu, Haichong; Deng, Ganzhen (Frontiers in Pharmacology, 2018)
Acute lung injury (ALI) is a progressive clinical disease with a high mortality rate, and characterized by an excessive uncontrolled inflammatory response. MicroRNAs (miRNAs) play a critical role in various human inflammatory diseases, and have been recognized as important regulators of inflammation. However, the regulatory mechanisms mediated by miRNAs involved in Lipopolysaccharide (LPS)-induced inflammation in ALI remain hazy. In this study, we found that miR-181a expression in the lung tissues of ALI mice and LPS-stimulated RAW 264.7 macrophages is dramatically reduced. We also show that over-expression of miR-181a significantly decreased the production of inflammatory cytokines, such as IL-1β, IL-6, and TNF-α, whereas inhibition of miR-181a reversed this decrease. Moreover, miR-181a inhibits NF-κB activation and accumulation of reactive oxygen species (ROS) by targeting TLR4 expression. We further verify that miR-181a suppresses TLR4 expression by binding directly to the 3′-UTR of TLR4. Therefore, we provide the first evidence for the negative regulation of miR-181a in LPS-induced inflammation via the suppression of ROS generation and TLR4-NF-κB pathway.